A Descriptive Study On The Assessment Of Knowledge Among Staff Nurses On Parenteral Nutrition Administration In A Tertiary Care Hospital At Salem District (International Journal of Food and Nutritional Sciences, 2023)
The modem era has achieved various bench marks in the field of health care. To meet the expectations and to face the tough situations, the nurses also need to be knowledgeable and competent in all spheres of handling critically ill patients. A descriptive study was conducted to gain insight into nurse's knowledge related to Parenteral Nutrition administration in a tertiary care hospital at Salem district